1988
DOI: 10.1161/01.res.62.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Monohydroxyeicosatetraenoic acids (5-HETE and 15-HETE) induce pulmonary vasoconstriction and edema.

Abstract: 5-, 15-, and 12-HETE (monohydroxyeicosatetraenoic acids) are products of the lipoxygenation of arachidonic acid. We investigated their role as possible mediators of pulmonary vasoactivity and pulmonary edema. Pulmonary artery pressure (?"), capillary pressure (P ap ), the change in lung wet weight (Awt) from baseline, and capillary filtration coefficient (K,) (as a measure of vascular permeability) were determined following an intravenous injection of each mono-HETE in lungs perfused at constant flow with eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…In agreement, other studies have shown that a lack of NO (which has vasorelaxant properties in the pulmonary arteries) may also contribute to endothelial dysfunction, especially in pulmonary hypertension-induced HAPE (Bailey et al, 2010). In addition, we found significant increase in ROS-dependent 15-HETE and 12-HETE, which both are known to have vasoconstrictive properties (Burhop et al, 1988;Nishiyama et al, 1998;Yiu et al, 2003). The essential amino acid tryptophan, the biogenic amines serotonin, and SDMA, which all are supposed to have vasoconstrictive function in pulmonary vessels, also increased significantly during the high altitude stay.…”
supporting
confidence: 92%
“…In agreement, other studies have shown that a lack of NO (which has vasorelaxant properties in the pulmonary arteries) may also contribute to endothelial dysfunction, especially in pulmonary hypertension-induced HAPE (Bailey et al, 2010). In addition, we found significant increase in ROS-dependent 15-HETE and 12-HETE, which both are known to have vasoconstrictive properties (Burhop et al, 1988;Nishiyama et al, 1998;Yiu et al, 2003). The essential amino acid tryptophan, the biogenic amines serotonin, and SDMA, which all are supposed to have vasoconstrictive function in pulmonary vessels, also increased significantly during the high altitude stay.…”
supporting
confidence: 92%
“…Thus, CYP2S1 may divert the metabolism of arachidonic acid away from HETEs by converting HpETEs into oxoETEs and epoxy alcohols. This result is of interest because several studies suggest that 5-, 12-, and 15-HETEs are inflammatory mediators and that their levels are elevated in several inflammatory diseases such as asthma and arthrosclerosis (Burhop et al, 1988;Damon et al, 1989;Rubin and Mollison, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…15-HETE has also been observed to affect vascular reactivity, though it remains unclear whether it promotes vasoconstriction or vasodilation. One view holds that 15-HETE may have a direct vasoconstrictive effect, as evidenced by its role in pulmonary vasculature, 42,43 promote leukocyte activation and inhibit prostacyclin production. 44 The steady and sustained increase of 15-HETE in our study may help explain the concurrent increase in DBP and decreases in FMD.…”
Section: Discussionmentioning
confidence: 99%